Islamisation and Its Opponents in Java A Political, Social, Cultural and Religious History, c. 1930 to Present - Ricklefs, M.C (NUS Press, 2012)
The Javanese - one of the largest ethnic groups in the Islamic world - were once mostly 'nominal Muslims' with pious believers a minority and the majority seemingly resistant to Islam's call for greater piety. Over the tumultuous period analyzed here - from the 1930s to the 2000s - that society has changed profoundly to become an extraordinary example of the rising religiosity that marks the modern age.Islamisation and Its Opponents in Java draws on a formidable body of sources, including interviews, archival documents and a vast range of published material, to situate the Javanese religious experience. Winner of the Kahin Prize from the Association of Asia Studies, the study has considerable relevance for much wider contexts. The final section of the book, which considers the significance of Java's religious history in global contexts, shows how it exemplifies a profound contest of values in the universal human search for a better life.